Microcrystalline glass based on high-manganese electrolytic manganese residues and taking diopside as main crystalline phase as well as preparation method and application of microcrystalline glass

Through the method of doping high-manganese content electrolytic manganese slag and Fe2O3, a microcrystalline glass with dioprene as the main crystal phase was prepared, which solved the problem of resource utilization of high-manganese content electrolytic manganese slag and realized high-performance microcrystalline glass Preparation improves process operability and product performance.

CN119285235APending Publication Date: 2025-01-10GUANGDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411444771.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively treat electrolytic manganese slag with high manganese content, resulting in reduced performance of microcrystalline glass, complex process and high cost. The existing technology is mainly aimed at electrolytic manganese slag with low manganese content, and cannot meet the resource utilization of high manganese content. need.

Method used

The electrolytic manganese slag with high manganese content is doped with Fe2O3, and microcrystalline glass is prepared by high-temperature calcination and melting, mutagenesis phase, adjust the glass network structure, improve the physical and chemical properties of microcrystalline glass, and pass specific process parameters. Adjust to ensure excellent product performance.

Benefits of technology

It realizes efficient resource utilization of electrolytic manganese slag with high manganese content, and prepares microcrystalline glass with high volume density, bending strength, excellent acid and alkali resistance, and moderate thermal expansion coefficient, which improves the comprehensive performance of the product and the operability of the process. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005087420650000191
    Figure BDA0005087420650000191
  • Figure BDA0005087420650000201
    Figure BDA0005087420650000201
  • Figure HDA0005087420660000011
    Figure HDA0005087420660000011
Patent Text Reader

Abstract

The invention belongs to the technical field of industrial solid waste resource utilization, and discloses high-manganese electrolytic manganese residue-based glass ceramic with diopside as a main crystalline phase, and a preparation method and application thereof. The method comprises the following operation steps: calcining electrolytic manganese residues with high manganese content at a high temperature, cooling, crushing, sieving, uniformly mixing the obtained manganese residues with Fe2O3, heating from room temperature to 800 DEG C at a heating rate of 10 DEG C / min, then heating to 1400 DEG C at a heating rate of 5 DEG C / min, and preserving heat for 1-2 hours to obtain a glass melt; annealing the molten glass at 600 DEG C for 2 hours, and cooling to room temperature to obtain base glass; the obtained base glass is heated to 750-900 DEG C, heat preservation is conducted for 120-150 min, nucleation treatment is conducted, then heating is conducted to 1050-1150 DEG C, heat preservation is conducted for 120-150 min, crystallization treatment is conducted, finally cooling is conducted along with a furnace body to the room temperature, and the glass ceramics are obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of resource utilization of industrial solid waste, and particularly relates to a microcrystalline glass based on high-manganese electrolytic manganese slag and with diopside as the main crystal phase, and a preparation method and application thereof. Background Art

[0002] Manganese and its compounds are used in many industries and fields and are one of the important strategic metals. my country is the largest producer and consumer of electrolytic manganese, with a production capacity of 97% of the world's total. Electrolytic manganese slag is an acidic solid waste produced in the process of electrolytic manganese refining. The general disposal process is open-air stacking or landfilling. These methods not only occupy a large amount of land, but also may cause harmful soluble ions (Mn) to accumulate in the landfill due to inadequate waterproofing. 2+ 、Cd 2+ NH 4+ ) and other substances enter the environment, causing serious environmental pollution and ecological health threats.

[0003] The current mainstream means of resource utilization are to use electrolytic manganese slag as secondary materials to recycle valuable substances, or directly prepare them into products. For example, electrolytic manganese slag can be stabilized and resourced by stabilization / solidification, recovery of valuable elements, electric repair, making sewage treatment materials, construction, fertilizers and other functional materials. However, in the resource preparation process, there are still problems such as low utilization rate of electrolytic manganese slag solid waste, complex process flow, high processing cost, low process operability, poor process utilization prospects, and high toxicity of electrolytic manganese slag leaching after treatment.

[0004] For example, Mn can be leached by leaching method. 2+ When using CaO and NaHCO3 for solidification / stabilization, it has certain requirements for leaching conditions, and the method is not practical and has high leaching costs. 2+ The ions can achieve solidification and stabilization effects, but the released NH3 may cause secondary pollution, so secondary treatment is required, which increases the treatment cost. Therefore, a harmless method for resource utilization of electrolytic manganese slag solid waste that can be put into large-scale use is urgently needed.

[0005] The composition of electrolytic manganese slag is generally Al2O3, CaO, MgO, SiO2, MnO and other elements. The main elements are consistent with the important composition of CaO-MgO-Al2O3-SiO2 (CMAS) quaternary system microcrystalline glass in typical silicate glass. The alkaline metal oxides that may be contained in electrolytic manganese slag can be used as flux to reduce the melting temperature during glass preparation, thereby reducing the energy consumption of the process. Therefore, the preparation of microcrystalline glass from manganese slag has attracted more and more attention. The microcrystalline phase and glass phase in microcrystalline glass have the characteristics of high mechanical strength, high hardness, high chemical stability, high wear resistance and high heat resistance. Compared with metal materials, it has lower density but denser structure and lighter weight, and is favored by many industries.

[0006] The process of preparing microcrystalline by electrolytic manganese slag can achieve a solid waste utilization rate of up to 100%. After preparation, microcrystalline glass has good solidification effect on heavy metals, and the leaching toxicity is far lower than the national standard limit. The product can be used in many fields such as building main body aggregate, decorative wall, optics, etc. Comprehensive evaluation shows that the method of preparing microcrystalline glass by electrolytic manganese slag has high added value, wide application range, and excellent product performance. Therefore, the method of preparing microcrystalline glass by electrolytic manganese slag has become a hot field for the resource utilization of electrolytic manganese slag solid waste.

[0007] Most of the existing processes are aimed at preparing microcrystalline glass from electrolytic manganese slag with low manganese content. However, due to the different purification processes and sources of raw ore, the manganese content of actual manganese slag is too high. There is an urgent need for a preparation process for preparing microcrystalline glass from electrolytic manganese slag with high manganese content. Summary of the invention

[0008] In order to overcome the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing microcrystalline glass based on high manganese electrolytic manganese slag with diopside as the main crystal phase. Because in the present invention, when manganese is excessive, it will have a great impact on the glass network structure, thereby reducing product performance, and secondly, there is also a great challenge in adjusting the parameters of the preparation process; and because the diopside phase is the main mineral phase of the CMAS system, it is orthorhombic columnar in shape, and is mainly white-gray in color, and it has been proven in previous studies that it has a certain solidification effect on heavy metals and can enhance the physical and chemical performance of microcrystalline glass; therefore, using dopants to induce the high manganese CMAS system microcrystalline glass to form a diopside phase is the basic premise of the present invention. The present invention uses 80-100% high manganese content EMR tailings as raw materials, utilizes a melting method to prepare microcrystalline glass, dopes Fe2O3 (10-15wt%) to induce the formation of diopside phase, and confirms the parameters such as the phase transition process and physicochemical changes caused by the optimal Fe doping amount of the microcrystalline glass and the concentration gradient; the method has the advantages of a large manganese slag doping amount, easy acquisition of nucleating agents, simple operation process, controllable process and high product performance.

[0009] Another object of the present invention is to provide a microcrystalline glass prepared by the above preparation method.

[0010] Another object of the present invention is to provide an application of the above-mentioned microcrystalline glass.

[0011] The purpose of the present invention is achieved through the following technical solutions:

[0012] A method for preparing glass-ceramics based on high-manganese electrolytic manganese slag and with diopside as the main crystal phase comprises the following steps:

[0013] (1) calcining electrolytic manganese slag with a high manganese content at 800° C. for 2 hours; cooling to room temperature after calcination, crushing and sieving through a 200-mesh sieve to obtain manganese slag with uniform particle size; the electrolytic manganese slag with a high manganese content contains 20-23% by mass of MnO;

[0014] (2) after the manganese slag obtained in step (1) is uniformly mixed with the nucleating agent Fe2O3, the mixture is loaded into a corundum crucible, and the temperature is increased from room temperature to 800°C at a heating rate of 10°C / min, and then the temperature is increased to 1400°C at a heating rate of 5°C / min, and the mixture is kept at this temperature for 1-2 hours to clarify and homogenize the melt, thereby obtaining a glass melt; the amount of the nucleating agent Fe2O3 is 10-15% of the total mass of the manganese slag and the nucleating agent Fe2O3;

[0015] (3) pouring the glass melt obtained in step (2) into a graphite crucible, compacting and flattening it, annealing it at 600° C. for 2 h, and finally cooling it to room temperature to obtain a base glass;

[0016] (4) The base glass obtained in step (3) is heated to 750-850°C at a rate of 5°C / min, and kept at this temperature for 120-150 min for nucleation treatment. Subsequently, the base glass is further heated to 1050-1150°C at a rate of 5°C / min, and kept at this temperature for 120-150 min for crystallization treatment. Finally, the base glass is cooled to room temperature along with the furnace body to obtain microcrystalline glass.

[0017] The electrolytic manganese slag with high manganese content in step (1) contains the following components in mass percentage: SiO2 34-36%, CaO 24-27%, MnO 20-23%, Al2O3 6-8%, MgO 2-4%, and other components 2-12%; the other components include SO2, K2O, Na2O, Cr2O3, BaO and TiO2 with a mass percentage of 0-2%.

[0018] The corundum crucible in step (2) is an arc-shaped crucible, and the amount of manganese slag and nucleating agent Fe2O3 filled in the corundum crucible after being evenly mixed does not exceed 2 / 3 of the crucible capacity.

[0019] The temperature of the nucleation treatment in step (4) is 800-850°C, and the temperature of the crystallization treatment is 1100-1150°C; the insulation time is 120 minutes.

[0020] A microcrystalline glass based on high manganese electrolytic manganese slag and with diopside as the main crystal phase, prepared by the above preparation method, wherein the volume density of the microcrystalline glass is 3.03-3.56 g / cm 3 , flexural strength is 34.54-63.13MPa, acid resistance is 90.34-95.88%, alkali resistance is 99.06-99.98%, thermal expansion coefficient is 8.68-11.88×10 -6 / E.

[0021] The above-mentioned microcrystalline glass is prepared by mixing high manganese content electrolytic manganese slag with Fe2O3. The main crystal phase of the microcrystalline glass is diopside phase. In the microstructure, a network or branch-like interwoven dense structure can be observed, which not only has a strong encapsulation effect on heavy metals in the original slag, but also can improve the physical and chemical properties of the product.

[0022] The above-mentioned microcrystalline glass based on high manganese electrolytic manganese slag and diopside as the main crystal phase has high bending strength and excellent physical and chemical properties such as acid and alkali resistance and heat resistance. The microcrystalline glass can be used in industrial directions such as sewage structure materials, high-temperature insulation materials, and factory floor / wall paving materials.

[0023] The method of the present invention requires that the electrolytic manganese slag with high manganese content be calcined at 800°C for more than 2 hours before preparation, and that it be ground and evenly crushed through a 200-mesh sieve. This stage mainly removes some of the original impurities in the electrolytic manganese slag, such as sulfides, amides and moisture. After the above treatment, the XRD spectrum of the high manganese electrolytic manganese slag is as follows: Figure 1 shown.

[0024] In the method of the present invention, in step (2), the mixture of manganese slag and nucleating agent Fe2O3 is kept at a temperature of 1400°C or above for at least 1 hour, so as to make the mixture enter a molten state, disrupt the original arrangement order of particles, and at the same time remove the internal air to obtain a dense molten body.

[0025] In the method of the present invention, in step (3), the glass melt is cast and molded at room temperature, and a basic glass is obtained. In the supercooled state at room temperature, the originally randomly stacked particles in the melt will also tend to be transformed into a regular arrangement; at this time, there may be certain crystal nuclei inside the basic glass, and this step is conducive to subsequent thermal processing to make the crystal grow. The annealing temperature is maintained at 600°C for more than 2 hours to slowly cool the glass, eliminate the thermal stress generated by the rapid alternation of hot and cold inside the basic glass, change the structural state of the basic glass and improve the mechanical properties. The casting mold is made of graphite mold with a certain heat shock resistance material, and the mold remains stable and does not react with the glass at the annealing temperature.

[0026] At the nucleation and crystallization temperature, crystal nuclei are generated in the base glass and then the crystals grow rapidly to form high-crystallinity glass-ceramics.

[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0028] The present invention crushes the impurity-removing high-manganese electrolytic manganese slag crystals after high-temperature calcination, sieves them, mixes them evenly with the nucleating agent Fe2O3, and then melts them at high temperature to obtain glass liquid, which is pressed and formed in a specific mold and annealed to obtain basic glass, and the basic glass is nucleated and crystallized to obtain microcrystalline glass. The present invention uses high-manganese electrolytic manganese slag as the main raw material and uses Fe2O3 as a nucleating agent to induce diopside crystal phase and improve crystallinity. The obtained microcrystalline glass product has good physical and chemical properties: the product volume density is 3.03-3.56g / cm 3 , the volume density is greater than marble (2.5g / cm 3 ) and granite (2.6-3.3g / cm 3 ). The flexural strength is 34.54-63.13MPa, the acid resistance is 90.34-95.88%, the alkali resistance is about 99.06-99.98%, and the thermal expansion coefficient is 8.68-11.88×10 -6 / E. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the XRD spectrum of the calcined electrolytic manganese slag with high manganese content described in the present invention.

[0030] Figure 2 FE-SEM image of the glass-ceramics prepared in Example 1 (0Fe).

[0031] Figure 3 FE-SEM image of the glass-ceramics prepared in Example 2 (1Fe).

[0032] Figure 4 FE-SEM image of the glass-ceramics prepared in Example 3 (5Fe).

[0033] Figure 5FE-SEM image of the glass-ceramics prepared in Example 4 (10Fe).

[0034] Figure 6 FE-SEM image of the glass-ceramics prepared in Example 5 (15Fe).

[0035] Figure 7 FE-SEM image of the glass-ceramics prepared in Example 6 (20Fe).

[0036] Figure 8 FE-SEM image of the microcrystalline glass prepared in Example 7 (0.5Cr).

[0037] Fig. 9 FE-SEM image of the microcrystalline glass prepared in Example 11 (3.0Cr).

[0038] Fig.10 XRD diagrams of the glass-ceramics prepared in Examples 1-6, wherein 0Fe is Example 1; 1Fe is Example 2; 5Fe is Example 3; 10Fe is Example 4; 15Fe is Example 5; and 20Fe is Example 6.

[0039] Fig.11 XRD diagrams of the glass-ceramics prepared in Examples 7-11, wherein 0.5Cr is Example 7; 1.0Cr is Example 8; 1.5Cr is Example 9; 2.0Cr is Example 10; and 3.0Cr is Example 11.

[0040] Fig.12 XRD diagrams of the glass-ceramics prepared in Examples 12-17, wherein 1Bi is Example 12; 5Bi is Example 13; 10Bi is Example 14; 15Bi is Example 15; 20Bi is Example 16; and 30Bi is Example 17. DETAILED DESCRIPTION

[0041] The present invention will be described in further detail below in conjunction with the examples and accompanying drawings, but the embodiments of the present invention are not limited thereto. The equipment, instruments and reagents used in the present invention are commonly used in the art. It should be understood that the examples described herein are only used to explain the present invention and are not intended to limit the present invention.

[0042] Example 1

[0043] A method for preparing glass-ceramics based on high-manganese electrolytic manganese slag and with diopside as the main crystal phase comprises the following steps:

[0044] (1) heating the electrolytic manganese slag with high manganese content to 800° C. at a heating rate of 10° C. / min for calcining for 2 h; cooling to room temperature after calcination, crushing and passing through a 200-mesh sieve to obtain manganese slag with uniform particle size;

[0045] The electrolytic manganese slag with high manganese content contains the following components by mass percentage: SiO2 35.2%, CaO 26.2%, MnO 22%, Al2O3 6.5%, MgO 3.5%, and other components 6.6%;

[0046] (2) weighing 200 g of the manganese slag obtained in step (1) and filling it into a curved corundum crucible, with the filling amount not exceeding 2 / 3 of the crucible capacity, heating from room temperature to 800° C. at a heating rate of 10° C. / min, then heating to 1400° C. at a heating rate of 5° C. / min, and keeping the temperature for 1 h to clarify and homogenize the melt to obtain a glass melt;

[0047] (3) pouring the glass melt obtained in step (2) into a preheated graphite crucible, compacting and flattening it, annealing it in a muffle furnace at 600° C. for 2 h, and finally cooling it to room temperature to obtain a base glass;

[0048] (4) The base glass obtained in step (3) was heated to 850° C. at a rate of 5° C. / min, kept at this temperature for 120 min for nucleation treatment, then continued to be heated to 1100° C. at a rate of 5° C. / min, kept at this temperature for 120 min for crystallization treatment, and finally cooled to room temperature with the furnace body to obtain microcrystalline glass. The FE-SEM spectrum of the microcrystalline glass in Example 1 is as follows: Figure 2 As shown, the XRD scanning spectrum is as follows Figure 8 As shown in 0Fe.

[0049] Example 2

[0050] A method for preparing glass-ceramics based on high-manganese electrolytic manganese slag and with diopside as the main crystal phase comprises the following steps:

[0051] (1) heating the electrolytic manganese slag with high manganese content to 800° C. at a heating rate of 10° C. / min for calcining for 2 h; cooling to room temperature after calcination, crushing and passing through a 200-mesh sieve to obtain manganese slag with uniform particle size;

[0052] The electrolytic manganese slag with high manganese content contains the following components by mass percentage: SiO2 35.5%, CaO 2 6.4%, MnO 21.5%, Al2O3 6.3%, MgO 3.8%, and other components 6.5%;

[0053] (2) Weigh 198 g of the manganese slag obtained in step (1) and 2 g of Fe2O3, mix them evenly, and fill them in a curved corundum crucible, with the filling amount not exceeding 2 / 3 of the crucible capacity, and heat them from room temperature to 800°C at a heating rate of 10°C / min, then heat them to 1400°C at a heating rate of 5°C / min, and keep them warm for 1 h to clarify and homogenize the melt to obtain a glass melt;

[0054] (3) pouring the glass melt obtained in step (2) into a preheated graphite crucible, compacting and flattening it, annealing it in a muffle furnace at 600° C. for 2 h, and finally cooling it to room temperature to obtain a base glass;

[0055] (4) The base glass obtained in step (3) is heated to 850°C at a rate of 5°C / min, kept at this temperature for 120 min for nucleation treatment, then further heated to 1100°C at a rate of 5°C / min, kept at this temperature for 120 min for crystallization treatment, and finally cooled to room temperature with the furnace body to obtain microcrystalline glass. The FE-SEM spectrum of the microcrystalline glass in Example 2 is shown in FIG. Figure 3 As shown, the XRD scanning spectrum is as follows Figure 8 As shown in 1Fe.

[0056] Example 3

[0057] A method for preparing glass-ceramics based on high-manganese electrolytic manganese slag and with diopside as the main crystal phase comprises the following steps:

[0058] (1) heating the electrolytic manganese slag with high manganese content to 800° C. at a heating rate of 10° C. / min for calcining for 2 h; cooling to room temperature after calcination, crushing and sieving through a 200-mesh sieve to obtain manganese slag with uniform particle size;

[0059] The electrolytic manganese slag with high manganese content contains the following components by mass percentage: SiO2 35.8%, CaO 25.2%, MnO 22.6%, Al2O3 7.5%, MgO 2.6%, and other components 6.3%;

[0060] (2) Weigh 190 g of the manganese slag obtained in step (1) and 10 g of Fe2O3, mix them evenly, and fill them in a curved corundum crucible, with the filling amount not exceeding 2 / 3 of the crucible capacity, and heat them from room temperature to 800° C. at a heating rate of 10° C. / min, and then heat them to 1400° C. at a heating rate of 5° C. / min, and keep them warm for 1 h to clarify and homogenize the melt to obtain a glass melt;

[0061] (3) pouring the glass melt obtained in step (2) into a preheated graphite crucible, compacting and flattening it, annealing it in a muffle furnace at 600° C. for 2 h, and finally cooling it to room temperature to obtain a base glass;

[0062] (4) The base glass obtained in step (3) is heated to 850°C at a rate of 5°C / min, and kept at this temperature for 120 minutes for nucleation treatment, and then further heated to 1100°C at a rate of 5°C / min, and kept at this temperature for 120 minutes for crystallization treatment, and finally cooled to room temperature with the furnace body to obtain microcrystalline glass. The FE-SEM spectrum of the microcrystalline glass in Example 3 is shown in FIG. Figure 4 As shown, the XRD scanning spectrum is as follows Figure 8 As shown in 5Fe.

[0063] Example 4

[0064] A method for preparing glass-ceramics based on high-manganese electrolytic manganese slag and with diopside as the main crystal phase comprises the following steps:

[0065] (1) heating the electrolytic manganese slag with high manganese content to 800° C. at a heating rate of 10° C. / min for calcining for 2 h; cooling to room temperature after calcination, crushing and passing through a 200-mesh sieve to obtain manganese slag with uniform particle size;

[0066] The electrolytic manganese slag with high manganese content contains the following components by mass percentage: SiO2 34.8%, CaO 24.5%, MnO 23.2%, Al2O3 6.3%, MgO 3.8%, and other components 7.4%;

[0067] (2) Weigh 180 g of the manganese slag obtained in step (1) and 20 g of Fe2O3, mix them evenly, and fill them in a curved corundum crucible, with the filling amount not exceeding 2 / 3 of the crucible capacity, and heat them from room temperature to 800°C at a heating rate of 10°C / min, then heat them to 1400°C at a heating rate of 5°C / min, and keep them warm for 1 h to clarify and homogenize the melt to obtain a glass melt;

[0068] (3) pouring the glass melt obtained in step (2) into a preheated graphite crucible, compacting and flattening it, annealing it in a muffle furnace at 600° C. for 2 h, and finally cooling it to room temperature to obtain a base glass;

[0069] (4) The base glass obtained in step (3) is heated to 850°C at a rate of 5°C / min, kept at this temperature for 120 min for nucleation treatment, then further heated to 1100°C at a rate of 5°C / min, kept at this temperature for 120 min for crystallization treatment, and finally cooled to room temperature with the furnace body to obtain microcrystalline glass. The FE-SEM spectrum of the microcrystalline glass in Example 4 is shown in FIG. Figure 5 As shown, the XRD scanning spectrum is as follows Figure 8 As shown in 10Fe.

[0070] Example 5

[0071] A method for preparing glass-ceramics based on high-manganese electrolytic manganese slag and with diopside as the main crystal phase comprises the following steps:

[0072] (1) heating the electrolytic manganese slag with high manganese content to 800° C. at a heating rate of 10° C. / min for calcining for 2 h; cooling to room temperature after calcination, crushing and passing through a 200-mesh sieve to obtain manganese slag with uniform particle size;

[0073] The electrolytic manganese slag with high manganese content contains the following components by mass percentage: SiO2 36.3%, CaO 24.7%, MnO 22.8%, Al2O3 7.4%, MgO 4.8%, and other components 4%;

[0074] (2) Weigh 170 g of the manganese slag obtained in step (1) and 30 g of Fe2O3, mix them evenly, and fill them in a curved corundum crucible, with the filling amount not exceeding 2 / 3 of the crucible capacity, and heat them from room temperature to 800°C at a heating rate of 10°C / min, then heat them to 1400°C at a heating rate of 5°C / min, and keep them warm for 1 h to clarify and homogenize the melt to obtain a glass melt;

[0075] (3) pouring the glass melt obtained in step (2) into a preheated graphite crucible, compacting and flattening it, annealing it in a muffle furnace at 600° C. for 2 h, and finally cooling it to room temperature to obtain a base glass;

[0076] (4) The base glass is heated to 850°C at a rate of 5°C / min and kept at this temperature for 120 min for nucleation treatment, then heated to 1100°C at a rate of 5°C / min and kept at this temperature for 120 min for crystallization treatment, and finally cooled to room temperature with the furnace body to obtain microcrystalline glass. The FE-SEM spectrum of the microcrystalline glass in Example 5 is shown in FIG. Figure 6 As shown, the XRD scanning spectrum is as follows Figure 8 As shown in 15Fe.

[0077] Example 6

[0078] A method for preparing glass-ceramics based on high-manganese electrolytic manganese slag and with diopside as the main crystal phase comprises the following steps:

[0079] (1) heating the electrolytic manganese slag with high manganese content to 800° C. at a heating rate of 10° C. / min for calcining for 2 h; cooling to room temperature after calcination, crushing and sieving through a 200-mesh sieve to obtain manganese slag with uniform particle size;

[0080] The electrolytic manganese slag with high manganese content contains the following components by mass percentage: SiO2 34.6%, CaO 25.2%, MnO 20.8%, Al2O3 7.2%, MgO 2.6%, and other components 9.6%;

[0081] (2) Weigh 160 g of the manganese slag obtained in step (1) and 40 g of Fe2O3, mix them evenly, and fill them in a curved corundum crucible, with the filling amount not exceeding 2 / 3 of the crucible capacity, and heat them from room temperature to 800°C at a heating rate of 10°C / min, then heat them to 1400°C at a heating rate of 5°C / min, and keep them warm for 1 h to clarify and homogenize the melt to obtain a glass melt;

[0082] (3) pouring the glass melt obtained in step (2) into a preheated graphite crucible, compacting and flattening it, annealing it in a muffle furnace at 600° C. for 2 h, and finally cooling it to room temperature to obtain a base glass;

[0083] (4) The base glass is heated to 850°C at a rate of 5°C / min and kept at this temperature for 120 min for nucleation treatment, then heated to 1100°C at a rate of 5°C / min and kept at this temperature for 120 min for crystallization treatment, and finally cooled to room temperature with the furnace body to obtain microcrystalline glass. The FE-SEM spectrum of the microcrystalline glass in Example 6 is shown in FIG. Figure 7 As shown, the XRD scanning spectrum is as follows Figure 8 As shown in 20Fe.

[0084] Example 7

[0085] A method for preparing glass-ceramics based on high-manganese electrolytic manganese slag and with diopside as the main crystal phase comprises the following steps:

[0086] (1) heating the electrolytic manganese slag with high manganese content to 800° C. at a heating rate of 10° C. / min for calcining for 2 h; cooling to room temperature after calcination, crushing and passing through a 200-mesh sieve to obtain manganese slag with uniform particle size;

[0087] The electrolytic manganese slag with high manganese content contains the following components by mass percentage: SiO2 35.6%, CaO 25.6%, MnO 22.8%, Al2O3 6.7%, MgO 3.2%, and other components 6.1%;

[0088] (2) Weigh 199 g of the manganese slag obtained in step (1) and 1 g of Cr2O3, mix them evenly, and fill them in a curved corundum crucible, with the filling amount not exceeding 2 / 3 of the crucible capacity, and heat them from room temperature to 800°C at a heating rate of 10°C / min, then heat them to 1400°C at a heating rate of 5°C / min, and keep them warm for 1 h to clarify and homogenize the melt to obtain a glass melt;

[0089] (3) pouring the glass melt obtained in step (2) into a preheated graphite crucible, compacting and flattening it, annealing it in a muffle furnace at 600° C. for 2 h, and finally cooling it to room temperature to obtain a base glass;

[0090] (4) The base glass is heated to 900°C at a rate of 5°C / min and kept at this temperature for 120min for nucleation treatment, then heated to 1150°C at a rate of 5°C / min and kept at this temperature for 120min for crystallization treatment, and finally cooled to room temperature with the furnace body to obtain microcrystalline glass. The FE-SEM spectrum of the microcrystalline glass in Example 7 is shown in FIG. Figure 8 As shown, the XRD scanning spectrum is as follows Fig.11 As shown in 0.5Cr.

[0091] Example 8

[0092] A method for preparing glass-ceramics based on high-manganese electrolytic manganese slag and with diopside as the main crystal phase comprises the following steps:

[0093] (1) heating the electrolytic manganese slag with high manganese content to 800° C. at a heating rate of 10° C. / min for calcining for 2 h; cooling to room temperature after calcination, crushing and passing through a 200-mesh sieve to obtain manganese slag with uniform particle size;

[0094] The electrolytic manganese slag with high manganese content contains the following components by mass percentage: SiO2 35.2%, CaO 25.3%, MnO 21.2%, Al2O3 6.5%, MgO 3.6%, and other components 8.2%;

[0095] (2) Weigh 198 g of the manganese slag obtained in step (1) and 2 g of Cr2O3, mix them evenly, and fill them in a curved corundum crucible, with the filling amount not exceeding 2 / 3 of the crucible capacity, and heat them from room temperature to 800°C at a heating rate of 10°C / min, then heat them to 1400°C at a heating rate of 5°C / min, and keep them warm for 1 h to clarify and homogenize the melt to obtain a glass melt;

[0096] (3) pouring the glass melt obtained in step (2) into a preheated graphite crucible, compacting and flattening it, annealing it in a muffle furnace at 600° C. for 2 h, and finally cooling it to room temperature to obtain a base glass;

[0097] (4) The base glass is heated to 900°C at a rate of 5°C / min and kept at this temperature for 120 min for nucleation treatment, then heated to 1150°C at a rate of 5°C / min and kept at this temperature for 120 min for crystallization treatment, and finally cooled to room temperature with the furnace to obtain microcrystalline glass. The XRD scanning spectrum is shown in FIG. Fig.11 As shown in 1.0Cr.

[0098] Example 9

[0099] A method for preparing glass-ceramics based on high-manganese electrolytic manganese slag and with diopside as the main crystal phase comprises the following steps:

[0100] (1) heating the electrolytic manganese slag with high manganese content to 800° C. at a heating rate of 10° C. / min for calcining for 2 h; cooling to room temperature after calcination, crushing and passing through a 200-mesh sieve to obtain manganese slag with uniform particle size;

[0101] The electrolytic manganese slag with high manganese content contains the following components by mass percentage: SiO2 35.8%, CaO 26.3%, MnO 22.8%, Al2O3 6.6%, MgO 3.2%, and other components 5.3%;

[0102] (2) Weigh 197 g of the manganese slag obtained in step (1) and 3 g of Cr2O3, mix them evenly, and fill them in a curved corundum crucible, with the filling amount not exceeding 2 / 3 of the crucible capacity, and heat them from room temperature to 800°C at a heating rate of 10°C / min, then heat them to 1400°C at a heating rate of 5°C / min, and keep them warm for 1 h to clarify and homogenize the melt to obtain a glass melt;

[0103] (3) pouring the glass melt obtained in step (2) into a preheated graphite crucible, compacting and flattening it, annealing it in a muffle furnace at 600° C. for 2 h, and finally cooling it to room temperature to obtain a base glass;

[0104] (4) The base glass is heated to 900°C at a rate of 5°C / min and kept at this temperature for 120 min for nucleation treatment, then heated to 1150°C at a rate of 5°C / min and kept at this temperature for 120 min for crystallization treatment, and finally cooled to room temperature with the furnace to obtain microcrystalline glass. The XRD scanning spectrum is shown in FIG. Fig.11 As shown in 1.5Cr.

[0105] Example 10

[0106] A method for preparing glass-ceramics based on high-manganese electrolytic manganese slag and with diopside as the main crystal phase comprises the following steps:

[0107] (1) heating the electrolytic manganese slag with high manganese content to 800° C. at a heating rate of 10° C. / min for calcining for 2 h; cooling to room temperature after calcination, crushing and sieving through a 200-mesh sieve to obtain manganese slag with uniform particle size;

[0108] The electrolytic manganese slag with high manganese content contains the following components by mass percentage: SiO2 35.1%, CaO 25.8%, MnO 22.3%, Al2O3 6.6%, MgO 3.3%, and other components 6.9%;

[0109] (2) Weigh 196 g of the manganese slag obtained in step (1) and 4 g of Cr2O3, mix them evenly, and fill them in a curved corundum crucible, with the filling amount not exceeding 2 / 3 of the crucible capacity, and heat them from room temperature to 800°C at a heating rate of 10°C / min, then heat them to 1400°C at a heating rate of 5°C / min, and keep them warm for 1 h to clarify and homogenize the melt to obtain a glass melt;

[0110] (3) pouring the glass melt obtained in step (2) into a preheated graphite crucible, compacting and flattening it, annealing it in a muffle furnace at 600° C. for 2 h, and finally cooling it to room temperature to obtain a base glass;

[0111] (4) The base glass is heated to 900°C at a rate of 5°C / min and kept at this temperature for 120 min for nucleation treatment, then heated to 1150°C at a rate of 5°C / min and kept at this temperature for 120 min for crystallization treatment, and finally cooled to room temperature with the furnace to obtain microcrystalline glass. The XRD scanning spectrum is shown in FIG. Fig.11 As shown in 2.0Cr.

[0112] Embodiment 11

[0113] A method for preparing glass-ceramics based on high-manganese electrolytic manganese slag and with diopside as the main crystal phase comprises the following steps:

[0114] (1) heating the electrolytic manganese slag with high manganese content to 800° C. at a heating rate of 10° C. / min for calcining for 2 h; cooling to room temperature after calcination, crushing and passing through a 200-mesh sieve to obtain manganese slag with uniform particle size;

[0115] The electrolytic manganese slag with high manganese content contains the following components by mass percentage: SiO2 34.9%, CaO 26.7%, MnO 22.5%, Al2O3 7.6%, MgO 3.6%, and other components 4.7%;

[0116] (2) Weigh 194 g of the manganese slag obtained in step (1) and 6 g of Cr2O3, mix them evenly, and fill them in a curved corundum crucible, with the filling amount not exceeding 2 / 3 of the crucible capacity, and heat them from room temperature to 800°C at a heating rate of 10°C / min, then heat them to 1400°C at a heating rate of 5°C / min, and keep them warm for 1 h to clarify and homogenize the melt to obtain a glass melt;

[0117] (3) pouring the glass melt obtained in step (2) into a preheated graphite crucible, compacting and flattening it, annealing it in a muffle furnace at 600° C. for 2 h, and finally cooling it to room temperature to obtain a base glass;

[0118] (4) The base glass is heated to 900°C at a rate of 5°C / min and kept at this temperature for 120min for nucleation treatment, then heated to 1150°C at a rate of 5°C / min and kept at this temperature for 120min for crystallization treatment, and finally cooled to room temperature with the furnace body to obtain microcrystalline glass. The FE-SEM spectrum of the microcrystalline glass in Example 7 is shown in FIG. Fig. 9 As shown, the XRD scanning spectrum is as follows Fig.11 As shown in 2.0Cr.

[0119] Example 12

[0120] A method for preparing glass-ceramics based on high-manganese electrolytic manganese slag and with diopside as the main crystal phase comprises the following steps:

[0121] (1) heating the electrolytic manganese slag with high manganese content to 800° C. at a heating rate of 10° C. / min for calcining for 2 h; cooling to room temperature after calcination, crushing and passing through a 200-mesh sieve to obtain manganese slag with uniform particle size;

[0122] The electrolytic manganese slag with high manganese content contains the following components by mass percentage: SiO2 35.2%, CaO 25.4%, MnO 21.8%, Al2O3 7.6%, MgO 3.6%, and other components 6.4%;

[0123] (2) Weigh 198 g of the manganese slag obtained in step (1) and 2 g of Bi2O3, mix them evenly, and fill them in a curved corundum crucible, with the filling amount not exceeding 2 / 3 of the crucible capacity, and heat them from room temperature to 800° C. at a heating rate of 10° C. / min, and then heat them to 1400° C. at a heating rate of 5° C. / min, and keep them warm for 1 h to clarify and homogenize the melt to obtain a glass melt;

[0124] (3) pouring the glass melt obtained in step (2) into a preheated graphite crucible, compacting and flattening it, annealing it in a muffle furnace at 600° C. for 2 h, and finally cooling it to room temperature to obtain a base glass;

[0125] (4) The base glass is heated to 900°C at a rate of 5°C / min and kept at this temperature for 120 min for nucleation treatment, then heated to 1150°C at a rate of 5°C / min and kept at this temperature for 120 min for crystallization treatment, and finally cooled to room temperature with the furnace to obtain microcrystalline glass. The XRD scanning spectrum is shown in FIG. Fig.12 As shown in 1Bi.

[0126] Example 13

[0127] A method for preparing glass-ceramics based on high-manganese electrolytic manganese slag and with diopside as the main crystal phase comprises the following steps:

[0128] (1) heating the electrolytic manganese slag with high manganese content to 800° C. at a heating rate of 10° C. / min for calcining for 2 h; cooling to room temperature after calcination, crushing and passing through a 200-mesh sieve to obtain manganese slag with uniform particle size;

[0129] The electrolytic manganese slag with high manganese content contains the following components by mass percentage: SiO2 35.6%, CaO 25.4%, MnO 22.6%, Al2O3 7.1%, MgO 3.2%, and other components 6.1%;

[0130] (2) Weigh 190 g of the manganese slag obtained in step (1) and 10 g of Bi2O3, mix them evenly, and fill them in a curved corundum crucible, with the filling amount not exceeding 2 / 3 of the crucible capacity, and heat them from room temperature to 800° C. at a heating rate of 10° C. / min, and then heat them to 1400° C. at a heating rate of 5° C. / min, and keep them warm for 1 h to clarify and homogenize the melt to obtain a glass melt;

[0131] (3) pouring the glass melt obtained in step (2) into a preheated graphite crucible, compacting and flattening it, annealing it in a muffle furnace at 600° C. for 2 h, and finally cooling it to room temperature to obtain a base glass;

[0132] (4) The base glass is heated to 900°C at a rate of 5°C / min and kept at this temperature for 120 min for nucleation treatment, then heated to 1150°C at a rate of 5°C / min and kept at this temperature for 120 min for crystallization treatment, and finally cooled to room temperature with the furnace to obtain microcrystalline glass. The XRD scanning spectrum is shown in FIG. Fig.12 As shown in Figure 5.

[0133] Embodiment 14

[0134] A method for preparing glass-ceramics based on high-manganese electrolytic manganese slag and with diopside as the main crystal phase comprises the following steps:

[0135] (1) heating the electrolytic manganese slag with high manganese content to 800° C. at a heating rate of 10° C. / min for calcining for 2 h; cooling to room temperature after calcination, crushing and passing through a 200-mesh sieve to obtain manganese slag with uniform particle size;

[0136] The electrolytic manganese slag with high manganese content contains the following components by mass percentage: SiO2 34.9%, CaO 25.6%, MnO 20.6%, Al2O3 7.7%, MgO 2.7%, and other components 8.5%;

[0137] (2) Weigh 180 g of the manganese slag obtained in step (1) and 20 g of Bi2O3, mix them evenly, and fill them in a curved corundum crucible, with the filling amount not exceeding 2 / 3 of the crucible capacity, and heat them from room temperature to 800° C. at a heating rate of 10° C. / min, and then heat them to 1400° C. at a heating rate of 5° C. / min, and keep them warm for 1 h to clarify and homogenize the melt to obtain a glass melt;

[0138] (3) pouring the glass melt obtained in step (2) into a preheated graphite crucible, compacting and flattening it, annealing it in a muffle furnace at 600° C. for 2 h, and finally cooling it to room temperature to obtain a base glass;

[0139] (4) The base glass is heated to 900°C at a rate of 5°C / min and kept at this temperature for 120 min for nucleation treatment, then heated to 1150°C at a rate of 5°C / min and kept at this temperature for 120 min for crystallization treatment, and finally cooled to room temperature with the furnace to obtain microcrystalline glass. The XRD scanning spectrum is shown in FIG. Fig.12 As shown in 10Bi.

[0140] Embodiment 15

[0141] A method for preparing glass-ceramics based on high-manganese electrolytic manganese slag and with diopside as the main crystal phase comprises the following steps:

[0142] (1) heating the electrolytic manganese slag with high manganese content to 800° C. at a heating rate of 10° C. / min for calcining for 2 h; cooling to room temperature after calcination, crushing and sieving through a 200-mesh sieve to obtain manganese slag with uniform particle size;

[0143] The electrolytic manganese slag with high manganese content contains the following components by mass percentage: SiO2 35.2%, CaO 25.4%, MnO 21.8%, Al2O3 6.8%, MgO 3.4%, and other components 7.4%;

[0144] (2) Weigh 170 g of the manganese slag obtained in step (1) and 30 g of Bi2O3, mix them evenly, and fill them in a curved corundum crucible, with the filling amount not exceeding 2 / 3 of the crucible capacity, and heat them from room temperature to 800° C. at a heating rate of 10° C. / min, and then heat them to 1400° C. at a heating rate of 5° C. / min, and keep them warm for 1 h to clarify and homogenize the melt to obtain a glass melt;

[0145] (3) pouring the glass melt obtained in step (2) into a preheated graphite crucible, compacting and flattening it, annealing it in a muffle furnace at 600° C. for 2 h, and finally cooling it to room temperature to obtain a base glass;

[0146] (4) The base glass is heated to 900°C at a rate of 5°C / min and kept at this temperature for 120 min for nucleation treatment, then heated to 1150°C at a rate of 5°C / min and kept at this temperature for 120 min for crystallization treatment, and finally cooled to room temperature with the furnace to obtain microcrystalline glass. The XRD scanning spectrum is shown in FIG. Fig.12 As shown in 15Bi.

[0147] Example 16

[0148] A method for preparing glass-ceramics based on high-manganese electrolytic manganese slag and with diopside as the main crystal phase comprises the following steps:

[0149] (1) heating the electrolytic manganese slag with high manganese content to 800° C. at a heating rate of 10° C. / min for calcining for 2 h; cooling to room temperature after calcination, crushing and sieving through a 200-mesh sieve to obtain manganese slag with uniform particle size;

[0150] The electrolytic manganese slag with high manganese content contains the following components by mass percentage: SiO2 35.7%, CaO 26.6%, MnO 21.8%, Al2O3 7.5%, MgO 2.2%, and other components 6.2%;

[0151] (2) Weigh 160 g of the manganese slag obtained in step (1) and 40 g of Bi2O3, mix them evenly, and fill them in a curved corundum crucible, with the filling amount not exceeding 2 / 3 of the crucible capacity, and heat them from room temperature to 800° C. at a heating rate of 10° C. / min, and then heat them to 1400° C. at a heating rate of 5° C. / min, and keep them warm for 1 h to clarify and homogenize the melt to obtain a glass melt;

[0152] (3) pouring the glass melt obtained in step (2) into a preheated graphite crucible, compacting and flattening it, annealing it in a muffle furnace at 600° C. for 2 h, and finally cooling it to room temperature to obtain a base glass;

[0153] (4) The base glass is heated to 900°C at a rate of 5°C / min and kept at this temperature for 120 min for nucleation treatment, then heated to 1150°C at a rate of 5°C / min and kept at this temperature for 120 min for crystallization treatment, and finally cooled to room temperature with the furnace to obtain microcrystalline glass. The XRD scanning spectrum is shown in FIG. Fig.12 As shown in 20Bi.

[0154] Embodiment 17

[0155] A method for preparing glass-ceramics based on high-manganese electrolytic manganese slag and with diopside as the main crystal phase comprises the following steps:

[0156] (1) heating the electrolytic manganese slag with high manganese content to 800° C. at a heating rate of 10° C. / min for calcining for 2 h; cooling to room temperature after calcination, crushing and sieving through a 200-mesh sieve to obtain manganese slag with uniform particle size;

[0157] The electrolytic manganese slag with high manganese content contains the following components by mass percentage: SiO2 35.2%, CaO 25.8%, MnO 21.3%, Al2O3 6.7%, MgO 2.6%, and other components 8.4%;

[0158] (2) Weigh 140 g of the manganese slag obtained in step (1) and 60 g of Bi2O3, mix them evenly, and fill them in a curved corundum crucible, with the filling amount not exceeding 2 / 3 of the crucible capacity, and heat them from room temperature to 800° C. at a heating rate of 10° C. / min, then heat them to 1400° C. at a heating rate of 5° C. / min, and keep them warm for 1 h to clarify and homogenize the melt to obtain a glass melt;

[0159] (3) pouring the glass melt obtained in step (2) into a preheated graphite crucible, compacting and flattening it, annealing it in a muffle furnace at 600° C. for 2 h, and finally cooling it to room temperature to obtain a base glass;

[0160] (4) The base glass is heated to 900°C at a rate of 5°C / min and kept at this temperature for 120 min for nucleation treatment, then heated to 1150°C at a rate of 5°C / min and kept at this temperature for 120 min for crystallization treatment, and finally cooled to room temperature with the furnace to obtain microcrystalline glass. The XRD scanning spectrum is shown in FIG. Fig.12 As shown in Figure 30Bi.

[0161] The physical and chemical properties of the glass-ceramics obtained in Examples 1-6 were tested, and the results are shown in Table 1:

[0162] Table 1 Physical and chemical properties of glass-ceramics prepared in Examples 1-6

[0163]

[0164] It can be seen from Table 1 that the volume density of the glass-ceramics prepared by Examples 1-6 is between 3.03 and

[0165] 3.56g / cm 3 , the volume density is greater than marble (2.5g / cm 3 ) and granite (2.6-3.3g / cm 3 ). The bending strength is 34.54-63.13MPa, the acid corrosion resistance is 90.34-95.88%, the alkali corrosion resistance is about 99.06-99.98%, and the thermal expansion coefficient is 8.68-11.88×10 -6 / E. In addition, combining Table 1 and Fig.10 It can be seen that at a concentration of 5Fe, the main crystalline phase can be induced to transform into the diopside phase, and within the scope of the embodiment, the main crystalline phase is the diopside phase. Figure 2-7 It is shown that the microstructure changes greatly with the increase of Fe2O3 concentration. Figure 4 (Example 3) It can be seen that the grains begin to be refined. Figure 6(Example 5) Needle-like structures appear. Therefore, it is feasible to effectively improve the physical and chemical properties of the product by adjusting the ratio of electrolytic manganese slag through Fe2O3 doping. The prepared microcrystalline glass has excellent high temperature resistance and excellent acid and alkali resistance. The appropriate amount of Fe2O3 doping can also improve the bending strength of the product. Among them, the microcrystalline glass with a doping amount of Fe2O3 of 10-15% has the best comprehensive performance.

[0166] Table 2 Physical and chemical properties of glass-ceramics prepared in Examples 7-11

[0167]

[0168] It can be seen from Table 2 that the microcrystalline glass prepared by Examples 7-11 has a volume density of 3.08-3.29 g / cm 3 The bulk density is also greater than that of marble and granite, but slightly lower than that of iron doping in Examples 1-7. The flexural strength is 39.54-74.60MPa, the acid corrosion resistance is 89.80-93.00%, the alkali corrosion resistance is about 99.77-99.95%, and the thermal expansion coefficient is 1.64-2.27×10 -6 / E. Then Figure 8 , 9 It can be seen that the addition of Cr2O3 can lead to grain refinement in the microscopic morphology, but the needle-like structure that appears when the concentration of Fe2O3 is high is not obviously seen, which also explains why the bending strength of the microcrystalline glass increases while the main crystal phase does not change.

[0169] The diffraction pattern ( Fig.12 ) It can be seen that in Examples 12-17 under similar preparation processes, Bi2O3 is not even as effective as Cr2O3 in inducing the diopside secondary phase. In the XRD spectrum, it can be seen that there is still no obvious change as the concentration increases to 30Bi, and after peak comparison using software, no crystalline phase with a high correlation can be retrieved. Therefore, it can be considered that Bi2O3 is not suitable for the preparation of high manganese content CMAS system microcrystalline glass.

[0170] In summary, Fe2O3 can better induce diopside phase as the main crystalline phase, and prepare microcrystalline glass with better acid resistance and more energy saving, while Cr2O3 can induce microcrystalline glass to form diopside as a secondary crystalline phase. The effect of grain refinement can be observed in the microscopic morphology, while improving the mechanical properties of microcrystalline glass, and the relative heat resistance is also better. Bi2O3 has no obvious phase change process under the same preparation process conditions in the present invention, and the XRD spectrum shows few diffraction peaks, and the diffraction peaks do not change much with the increase of doping concentration. Bi2O3 is not suitable for the selection of the nucleating agent of the present invention.

[0171] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.

Claims

1. A method for preparing glass-ceramics based on high manganese electrolytic manganese slag and diopside as the main crystal phase, characterized in that The steps include: (1) calcining electrolytic manganese slag with a high manganese content at 800° C. for 2 hours; cooling to room temperature after calcination, crushing and sieving through a 200-mesh sieve to obtain manganese slag with uniform particle size; the electrolytic manganese slag with a high manganese content contains 20-23% by mass of MnO; (2) after the manganese slag obtained in step (1) is uniformly mixed with the nucleating agent Fe2O3, the mixture is loaded into a corundum crucible, and the temperature is increased from room temperature to 800°C at a heating rate of 10°C / min, and then the temperature is increased to 1400°C at a heating rate of 5°C / min, and the mixture is kept at this temperature for 1-2 hours to clarify and homogenize the melt, thereby obtaining a glass melt; the amount of the nucleating agent Fe2O3 is 10-15% of the total mass of the manganese slag and the nucleating agent Fe2O3; (3) pouring the glass melt obtained in step (2) into a graphite crucible, compacting and flattening it, annealing it at 600° C. for 2 h, and finally cooling it to room temperature to obtain a base glass; (4) The base glass obtained in step (3) is heated to 750-850°C at a rate of 5°C / min, and kept at this temperature for 120-150 min for nucleation treatment. Subsequently, the base glass is further heated to 1050-1150°C at a rate of 5°C / min, and kept at this temperature for 120-150 min for crystallization treatment. Finally, the base glass is cooled to room temperature along with the furnace body to obtain microcrystalline glass.

2. The method for preparing glass-ceramics based on high manganese electrolytic manganese slag and with diopside as the main crystal phase according to claim 1, characterized in that: The electrolytic manganese slag with high manganese content in step (1) contains the following components in mass percentage: SiO2 34-36%, CaO 24-27%, MnO 20-23%, Al2O3 6-8%, MgO 2-4%, and other components 2-12%; the other components include SO2, K2O, Na2O, Cr2O3, BaO and TiO2 with a mass percentage of 0-2%.

3. The method for preparing glass-ceramics based on high manganese electrolytic manganese slag and with diopside as the main crystal phase according to claim 1, characterized in that: The corundum crucible in step (2) is an arc-shaped crucible, and the amount of manganese slag and nucleating agent Fe2O3 filled in the corundum crucible after being evenly mixed does not exceed 2 / 3 of the crucible capacity.

4. The method for preparing glass-ceramics based on high manganese electrolytic manganese slag and with diopside as the main crystal phase according to claim 1, characterized in that: The temperature of the nucleation treatment in step (4) is 800-900°C, and the temperature of the crystallization treatment is 1100-1150°C; the insulation time is 120 minutes.

5. A glass-ceramic based on high manganese electrolytic manganese slag and having diopside as the main crystal phase, prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The volume density of the microcrystalline glass is 3.03-3.56 g / cm 3 , flexural strength is 34.54-63.13MPa, acid resistance is 90.34-95.88%, alkali resistance is 99.06-99.98%, thermal expansion coefficient is 8.68-11.88×10 -6 / E.

6. Application of the microcrystalline glass based on high manganese electrolytic manganese slag and with diopside as the main crystal phase according to claim 5 in sewage structure materials, high-temperature thermal insulation materials, and factory floor or wall paving materials.